Characteristic Immune Dynamics in COVID-19 Patients with Cardiac Dysfunction - Gonzalez, Filipe André (2022)
Funding Information: Type of funding sources: Foundation—015_595935779—Foundation for Science and Technology (FCT), in collaboration with the Agency for Clinical Research and Biomedical Innovation (AICIB) opened special funding, “RESEARCH 4 COVID-19”, to R&D projects and initiatives that respond to the needs of the National Health Service (SNS) as a response to this and future pandemics in a very short time Horizon. Project: “Early recognition of cardiac injury associated with COVID-19 and clinical outcomes”.